Implementation of High Speed Self Switching Frequency Agile RADAR - K Jansi Lakshmi; K Surya Narayana Reddy (International Journal of Reconfigurable and Embedded Systems (IJRES), 2014)
The radar has to resist diversified jamming; High Speed self-adaptive frequency   agility   is   an   important   and   effective function  for radars to resist jamming.  The procedure to achieve this function are described, and the function is realized with FPGA using Hardware description  Language, the validity is proved by on- line sampling and simulation. The High speed self-adaptive frequency agility module can analyze the type of jamming to select  transmitting  frequency  to avoid the frequencies which have interference, under frequency       diversity  and  fixed  frequency, respectively. The   general   application   on   a   searching   radar shows that the module has good real-time and anti- jamming capacity.